2015
DOI: 10.1073/pnas.1515484112
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin supplementation in pregnant mice prevents the adverse effects of maternal obesity on placental function and fetal growth

Abstract: Mothers with obesity or gestational diabetes mellitus have low circulating levels of adiponectin (ADN) and frequently deliver large babies with increased fat mass, who are susceptible to perinatal complications and to development of metabolic syndrome later in life. It is currently unknown if the inverse correlation between maternal ADN and fetal growth reflects a cause-and-effect relationship. We tested the hypothesis that ADN supplementation in obese pregnant dams improves maternal insulin sensitivity, resto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
136
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(146 citation statements)
references
References 44 publications
3
136
0
1
Order By: Relevance
“…Adiponectin is an adipocyte-derived hormone that has been suggested to mediate maternal obesity-altered fetal growth [23, 44]. Recent studies, including our work, demonstrated that adiponectin is not expressed in the placenta and cannot pass through the placental barrier [23, 33].…”
Section: Discussionmentioning
confidence: 73%
“…Adiponectin is an adipocyte-derived hormone that has been suggested to mediate maternal obesity-altered fetal growth [23, 44]. Recent studies, including our work, demonstrated that adiponectin is not expressed in the placenta and cannot pass through the placental barrier [23, 33].…”
Section: Discussionmentioning
confidence: 73%
“…1). Drivers associated with maternal insulin resistance might include excess fuel supply, inflammation, hormones (for example adiponectin 44 ) and fetal hypoxia, as discussed later. In humans, increased maternal insulin resistance, independent of excessive gestational weight gain, mediates fetal adiposity 45 , and increased maternal insulin resistance in mice results in progressive development of postnatal lipid deposition in the offspring 46 .…”
Section: Intrauterine Clues For Nafld Riskmentioning
confidence: 99%
“…These aspects include insulin and adipokines, such as leptin and 195 adiponectin as well as cytokines [62,63] and placental nutrient sensing pathways [65]. 202…”
Section: Maternal Overweight and Obesity 192 193mentioning
confidence: 99%